KAJIAN POTENSI PENGGUNAAN MODUL NRF24L01 SEBAGAI BEL NIRKABEL OTOMATIS BERBASIS ARDUINO - Firliansyah, Tegar; Pauzan, Muh; Yanti, Indri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
An investigation of the potential for making wireless doorbells based on the NRF24L01 module has been studied. The transmitter and receiver modules are made, the transmitter module consists of an Arduino as a controller, an NRF24L01 module as a signal transmitter and an HC SR-04 ultrasonic sensor as a detector for guests in front of the house. The receiver module consists of an Arduino, NRF24L01 as a receiver of signals sent from the transmitter module and a buzzer which is the functions is to provide notification to the home owner. The NRF24L01 module is used because of its large communication distance, up to 100 m. Besides that the NRF24L01 module can communicate with more than one NRF24L01 modules. Based on the results of testing the performance of the device, the longest communication distance between the transmitter module and the receiver module was obtained in conditions without obstructions, clear glass barriers, cardboard barriers and house wall barriers of xx, xx, xx, xx, respectively. Based on the current consumption test, the transmitter and receiver modules use 50.21 and 60.23 mA respectively. The power source of the transmitter module is from two Li-Ion batteries with a total capacity of 600 mAh. Based on the calculations made, the battery with this capacity can last on the transmitter module for 35.22 hours. While the receiver module is directly connected to the PLN power source.